Small breast epithelial mucin tumor tissue expression is associated with increased risk of recurrence and death in triple-negative breast cancer patients - Liu, Liang (BioMed Central, 2013)
BACKGROUND: Small breast epithelial mucin (SBEM) has been implicated in tumor genesis and micrometastasis in breast cancer. Triple-negative breast cancer (TNBC) was characterized by high incidence in young women,early relapse and a very poor prognosis. The aim of this study was to evaluate the association of SBEM expression in tissues of TNBC with disease-free survival (DFS) and overall survival (OS). METHODS: SBEM protein expression was detected in 87 available formalin-fixed paraffin-embedded (FFPE) tissue specimens from TNBC patients by means of immunohistochemistry (IHC). We analyzed the correlation between the SBEM protein expression and DFS and OS during a 5 year follow-up period, respectively. And a SBEM cut-off value of prognosis was established associated with DFS and OS. SBEM was analyzed against other risk factors in multivariate analysis. RESULTS: SBEM 3+ score was cut-off value of prognosis and significantly correlated with DFS (p = 0.000) and OS (p = 0.001) in TNBC patients. There was a marked associations (p <0.05) between SBEM 3+ score and tumor size, grade, node status, TNM stage and Ki67. Multivariate analysis showed that patients with SBEM 3+ represented a higher risk of recurrence and mortality than those with a lower SBEM expression (HR = 3.370 with p = 0.008 for DFS and HR = 4.185 with p = 0.004 for OS). CONCLUSIONS: SBEM is an independent risk predictor and may offer utility as a prognostic marker in TNBC patients. VIRTUAL SLIDES: http://www.diagnosticpathology.diagnomx.eu/vs/1624613061936917